Circulating Glutathione Peroxidase-3 in Elderly—Association with Renal Function, Cardiovascular Mortality, and Impact of Selenium and Coenzyme Q10 Supplementation - Jan Alexander; Jan Olav Aaseth; Lutz Schomburg; Thilo Samson Chillon; Anders Larsson; Urban Alehagen (Antioxidants)
Low-selenium status was associated with impaired renal function, which improved after selenium and coenzyme Q10 supplementation in an RCT. Here, we evaluated serum glutathione peroxidase-3 (GPx3) and its relation to serum selenium, selenoprotein P (SELENOP), renal function, mortality, and the impact of supplementation, which are all important, especially in elderly individuals. In total, 383 study participants (197 receiving selenium yeast and coenzyme Q10 and 186 on a placebo) were evaluated. We applied benchmark dose modelling to determine GPx3 saturation, ANCOVA, Kaplan–Meier, and multivariate Cox proportional regression analyses for mortality evaluations. Selenium and GPx3 activity were modestly correlated. In comparison with SELENOP, GPx3 levelled off at a much lower value, 100 vs. 150 µg Se/L. GPx3 was associated with renal function, but not SELENOP. Supplementation increased glomerular function by ≈23% with an increase in GPx3. Being low in GPx3 displayed twice the risks of mortality in both placebos and active treatments. At serum selenium <100 µg/L, GPx3 activity was dependent on both selenium status and renal function. As renal function is reduced in the elderly, GPx3 is not an appropriate marker of selenium status. Low GPx3 was associated with an increased risk of mortality dependent of selenium status and independent of renal function.